Endothelial Shear Stress and Platelet FcγRIIa Expression in Intracranial Atherosclerotic Disease - Liebeskind, David S.; Hinman, Jason D.; Kaneko, Naoki; Kitajima, Hiroaki; Honda, Tristan; De Havenon, Adam H.; Feldmann, Edward; Nogueira, Raul G.; Prabhakaran, Shyam; Romano, Jose G.; Callas, Peter W.; Schneider, David J. (Frontiers in Neurology, 2021)
Intracranial atherosclerotic disease (ICAD) has been characterized by the degree of arterial stenosis and downstream hypoperfusion, yet microscopic derangements of endothelial shear stress at the luminal wall may be key determinants of plaque growth, vascular remodeling and thrombosis that culminate in recurrent stroke. Platelet interactions have similarly been a principal focus of treatment, however, the mechanistic basis of anti-platelet strategies is largely extrapolated rather than directly investigated in ICAD. Platelet FcγRIIa expression has been identified as a potent risk factor in cardiovascular disease, as elevated expression markedly increases the risk of recurrent events. Differential activation of the platelet FcγRIIa receptor may also explain the variable response of individual patients to anti-platelet medications. We review existing data on endothelial shear stress and potential interactions with the platelet FcγRIIa receptor that may alter the evolving impact of ICAD, based on local pathophysiology at the site of arterial stenosis. Current methods for quantification of endothelial shear stress and platelet activation are described, including tools that may be readily adapted to the clinical realm for further understanding of ICAD.